Pengembangan Karakter Siswa melalui Pembelajaran PKn Berbasis Kontekstual - Ronggo Warsito; Bayu Indrayanto; Dhiva Maulida Rizqi Nur’aini (LPPM Universitas Widya Dharma, 2023)
The aims of this research are 1) to find out the reasons why contextual-based Civics learning is relevant in efforts to develop student character, 2) to find obstacles that arise in developing student character through contextual-based Civics learning, and 3) to find solutions that can taken in developing student character through contextual-based Civics learning. This research uses a qualitative paradigm. The research subjects were students and teachers of Civics class VIIIA at SMP Negeri 1 Simo, Boyolali. Data validity uses triangulation of sources and methods. Data collection techniques use questionnaires, interviews, observation and documentation. The data analysis technique uses interactive analysis. The results of the research show, first, the reasons that contextual-based Civics learning is relevant to developing student character because (1) the learning process activates all student potential, both cognitive, affective and psychomotor, (2) the learning material is relevant to everyday life, and (3) character develops because learning is relevant to students' real world. Second, the obstacles that arise in developing student character through contextual-based Civics learning are that students were previously not accustomed to relating class material to the environment and students' daily lives. Third, solutions that can be taken in developing student character through contextual-based Civics learning are to always link learning material in class with the environment and students' daily lives. Keywords: character; contextual; Civics learning.